2016
DOI: 10.1016/j.infbeh.2016.06.010
|View full text |Cite
|
Sign up to set email alerts
|

Goodness of fit between prenatal maternal sleep and infant sleep: Associations with maternal depression and attachment security

Abstract: The current study prospectively examined the ways in which goodness of fit between maternal and infant sleep contributes to maternal depressive symptoms and the mother-child relationship across the first years of life. In a sample of 173 mother-child dyads, maternal prenatal sleep, infant sleep, maternal depressive symptoms, and mother-child attachment security were assessed via selfreport, actigraphy, and observational measures. Results suggested that a poor fit between mothers' prenatal sleep and infants' sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 40 publications
1
16
0
Order By: Relevance
“…The questionnaire was developed by Simard, the first author, who is a child psychologist and has research expertise in child sleep and the parent‐child relationship. The questions on parents’ prenatal and the child's sleep (Table 1) were inspired by the idea that a greater decline in sleep quantity during the perinatal period or a mismatch with the infant's sleep may be a source of parental distress (Newland et al., 2016; Tomfohr et al., 2015). The question on the impacts of lack of sleep was constructed to cover a variety of life domains (e.g., romantic relationship; Medina et al., 2009), and to shed light on life functioning and satisfaction rather than focussing on anxiety or depression.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The questionnaire was developed by Simard, the first author, who is a child psychologist and has research expertise in child sleep and the parent‐child relationship. The questions on parents’ prenatal and the child's sleep (Table 1) were inspired by the idea that a greater decline in sleep quantity during the perinatal period or a mismatch with the infant's sleep may be a source of parental distress (Newland et al., 2016; Tomfohr et al., 2015). The question on the impacts of lack of sleep was constructed to cover a variety of life domains (e.g., romantic relationship; Medina et al., 2009), and to shed light on life functioning and satisfaction rather than focussing on anxiety or depression.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, there is evidence that mothers who perceive that they had better prenatal sleep are more distressed by postpartum sleep loss. For instance, in a study assessing the “goodness of fit” between maternal and infant sleep, poorer infant sleep was associated with maternal depression only among mothers who reported sleeping longer in the prenatal period (Newland et al., 2016). Thus far, much of the research on the effects of postpartum sleep disturbances has focused on depression and anxiety.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first focused on the relationship between mothers' quality of sleep, the number of hours that they slept, and the number of times that they attended to their newborn infant during the night. Previous research has shown that the goodness of fit between mothers' and infants' sleep predicts maternal depression and attachment security (Newland, Parade, Dickstein, & Seifer, 2016), and that the frequency with which mothers attend to their babies informs their subjective sleep quality (Gress et al, 2010). Here, we predicted that mothers, who slept more hours and attended to their baby fewer times compared to other mothers (i.e.…”
Section: Introductionmentioning
confidence: 92%
“…Disturbed and inadequate sleep in infants in the first year of life can be problematic with approximately one‐third of parents reporting an infant that requires parental assistance for initiating and/or reinitiating sleep . Such sleep disturbance can be problematic for the whole family and is related to a substantial increase in the risk of parental depression and anxiety, poorer parent/infant attachment early cessation of breastfeeding, significant sleepiness, fatigue and subsequently poorer psychosocial functioning, parental and marital discord and even an increased incidence of child abuse such as shaken baby syndrome …”
mentioning
confidence: 99%